Dietary supplementation with pyrroloquinoline quinone promotes growth, relieves weaning stress, and regulates metabolism of piglets compared with adding zinc oxide - Chenyu Shi; Zirou Yu; Zijie Wang; Ran Ning; Caiyun Huang; Youjun Gao; Fenglai Wang (Animal Nutrition, 2023)
Hindered growth often occurs because of psychological and environmental stress during the weaning period of piglets. This study aimed to compare the effects of growth performance, diarrhea indices, digestibility of nutrients, antioxidant capacity, neurotransmitters levels and metabolism of weaned pigs fed diets supplemented with pyrroloquinoline quinone (PQQ) and zinc oxide (ZnO). Pigs weaned at d 28 (n = 108) were fed with three different diets including: the basal diet (CTRL group), the basal diet supplemented with 3.0 mg/kg PQQ (PQQ group) and the basal diet containing 1,600 mg/kg ZnO (ZNO group). During the first 14 d, weaned pigs fed the diet supplemented with PQQ and ZnO decreased feed to gain ratio and diarrhea rate (P < 0.01). Compared with the CTRL group, average daily gain was increased in weaned pigs in the PQQ group from d 15 to 28 (P = 0.03). Compared with the CTRL group, pigs fed PQQ and ZnO supplemented diets showed improved apparent total tract digestibility (ATTD) of nutrients (P ≤ 0.05). During the overall experimental period, the concentration of malondialdehyde was decreased in plasma of pigs in the PQQ and ZNO groups compared with the CTRL group (P < 0.05). At d 28, the concentration of vasoactive intestinal peptide (VIP) and calcitonin gene-related peptide (CGRP) was lower in plasma of weaned pigs in the PQQ and ZNO groups compared with the CTRL group (P < 0.05). There was no difference between the PQQ and ZNO group in growth performance, ATTD of nutrition, antioxidant capacity and neurotransmitters levels. PQQ increased 3-methoxy-4-hydroxymandelate (P < 0.05) compared with the CTRL group. According to metabolomic analysis, erucamide, formononetin and 3-methyl-L-histidine were up-regulated in the PQQ group (P < 0.05). Compared with the CTRL group, aloesin and dibutyl adipate were down-regulated in the PQQ group (P < 0.05). In conclusion, similar to ZnO, PQQ improves growth performance, digestibility of nutrients, antioxidant capacity, neuromodulation and metabolism of weaned pigs. Thus, like ZnO, PQQ can be effectively applied in weaned pigs.